Synthesis and characterization of 6,8-di-tert-butyl-3-[p-(propynyl) phenoxy]coumarin substituted phthalocyanines and investigation of their photophysical and photochemical properties - (:unkn) unknown (ELSEVIER SCIENCE SA, 2017)
The new compound, 6,8-di-tert-butyl-3-[p-(propynyl)phenoxy]coumarin 2 was prepared by the reaction of 6,8-di-tert-butyl-3-(p-hydroxyphenyl)coumarin 1 with propargyl bromide. The synthesized 6,8-di-tert-butyl-3-[p-(propynyl)phenoxy]coumarin was reacted with tetra-iodo zinc(II) (3) or tetra-iodo indium(III) acetate (4) phthalocyanines by the Sonogashira coupling reaction for the synthesis of the coumarin substituted phthalocyanines 5 and 6, respectively. These phthalocyanines are the first examples of the coumarin substituted phthalocyanines connected by ethynyl bond. All novel compounds synthesized in this study were fully characterized by general spectroscopic techniques such as FT-IR, UV-vis, H-1 NMR, mass and elemental analysis as well. The photophysicochemical and spectral properties of zinc(II) and indium(III)OAc phthalocyanines (5 and 6) were investigated in dimethylsulfoxide (DMSO) solutions. The complexes (5 and 6) showed well solubility in most of organic solvents such as dichloromethane, THF, chloroform, DMF and DMSO. These phthalocyanines (5 and 6) exhibited good singlet-oxygen generation (Phi(Delta) = 0.96 for 6 and Phi(Delta) = 0.62 for 5) and appropriate photodegradation quantum yields (Phi(d) = 0.45x10(-5) for 5 and Phi(d) = 0.43x10(-5) for 6) in DMSO. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Coumarin; Phthalocyanine; Ethynyl; Fluorescence; Singlet oxygen; Photodegradation; Sonogashira reaction